Hydrological impacts of inflow and land-use changes in the Gorai River catchment, Bangladesh - Bharati, Luna; Jayakody, Priyantha (Informa UK Limited, 2011)
This study looks at the changes in water balance in the Gorai River Catchment in the Bangladesh delta before and after operationalization of Farakka Barrage. Results show that in ow into the catchment has decreased, but major changes in land use within the catchment have also impacted runoff. Model scenarios demonstrate that although increasing in ow from upstream is the most effective method to increase dry season ows into the delta, reduction in cultivation of water-intensive crops would provide an alternative solution.